Polyphenolic constituents, antioxidant and hypoglycaemic potential of leaf extracts of Acalypha godseffiana from Eastern Nigeria: In vitro study - Anita K. Asekunowo; Anofi O.T. Ashafa; Omobola Okoh; Olayinka T. Asekun; Oluwole B. Familoni (AOSIS, 2019)
Background: Acalypha godseffiana is an important plant used as an ornamental and herbs; its leaves are used in the management of diseases like diabetes in Eastern Nigeria. Aim: The study aims at linking the hypoglycemic activity extracts of leaves of A. godseffiana to their polyphenolic contents. Setting: Fresh leaves of A. godseffiana were obtainedfrom Imo State, Nigeria, identified in University of Lagos Herbarium, air-dried, pulverized and kept for investigations. Method: The phytochemical compositions and antioxidant potentials of acetone, aqueous, ethanol and methanol extracts of A. godseffiana were determined using adopted methods. An in-vitroapproach was used to evaluate the hypoglycemic potentials of the extracts on α-amylase and α-glucosidase enzymes. The mechanism of inhibitions was studied using the Lineweaver-Burk plot. Results: Antioxidant results revealed that total antioxidant capacity of the acetone extract (IC50: 0.34 mg/mL) showed better activity compared to the standards (silymarin 0.52 mg/mL; gallic acid 0.51 mg/mL). Thehypoglycemic findings confirmed that acetone extract demonstrated strong and mild inhibitory potential against α-amylase and α-glucosidase respectively, showing concentration dependent with IC50 values of 2.33 mg/mL and 0.13 mg/mL. The observed hypoglycemic and antioxidant potentials of acetone extract of A. godseffiana correlate to its high polyphenolic contents which include phenols (133.20 mg gallic acid g-1), flavonoid (350.60 mg quercetin g-1) and tannins (264.67 mg catechin g-1). The mechanisms of action exhibited by the acetone extractwere uncompetitive and mixed non-competitive which can be attributed to its inhibitory properties on α-glucosidase and α-amylase respectively. Conclusion: The results obtained from this study validate the acetone leaves extract of A. godseffiana as potential agent in management of sugar related disorder.